Freedom of expression and right to be forgotten: The counter balance in law and practice - Ngo, Huong (Vietnam national university, Hanoi, 2020)
This paper addresses the extent which freedom of expression (FOE) and right to be forgoten (R2F) have been contested in law making. The international standards and norms of FOE are established. The review of law and practice of European system, USA and some states in ASEAN like Indonesia, Singapore, Thailand and Vietnam which are selected to represent different state of practice and laws. The analysis shows these states are variably political committed to FOE in laws. But the challenges for FOE is placed by evolving need to recognise right to be forgotten is placed by emerging use of artificial intellectuals. States with strong values on freedom of expression have made changes in protecting right to be forgotten in laws, including privacy and personal data protection and internet use. Some states in ASEAN, though recognise FOE in their constitutions and laws, but often make non-compliance with international standards on the ground of national security needs. Neither of these positions seems generally justified. Research implications include a need for freedom of expression and right to be forgotten to have norms and standards as basic human rights, in particular practice of restricting this freedom which imply that states needs to have a common understanding on FOE, R2F and to provide sufficient protection on personal privacy and the extent to which states can pose restrictions by legitimate manner in law.